2019
DOI: 10.1096/fj.201901314rr
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal brush cells release acetylcholine in response to bitter tastants for paracrine and autocrine signaling

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes. AbstractFor protection from inhaled pathogens many strategies have evolved in the airways such as mucociliary clearance and cough. We have previously shown that protective respiratory reflexes to locally released bacterial bitter "taste" substances are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
102
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(111 citation statements)
references
References 54 publications
(267 reference statements)
7
102
1
1
Order By: Relevance
“…However, the biosynthesis and release of ACh in tuft cells remains largely unknown. So far, only the expression of ChAT on tuft cells, and the release of ACh from tuft cells have been experimentally validated ( Ting and von Moltke, 2019 ; Hollenhorst et al, 2020 ). On account of the absence of VAChT and CHT1 in gastrointestinal tuft cells, we highly deduce that, except the canonical biosynthesis pathway of ACh, tuft cells may synthesize and release ACh through different pathways ( Figure 1 ).…”
Section: Acetylcholine Biosynthesis and Release In Tuft Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the biosynthesis and release of ACh in tuft cells remains largely unknown. So far, only the expression of ChAT on tuft cells, and the release of ACh from tuft cells have been experimentally validated ( Ting and von Moltke, 2019 ; Hollenhorst et al, 2020 ). On account of the absence of VAChT and CHT1 in gastrointestinal tuft cells, we highly deduce that, except the canonical biosynthesis pathway of ACh, tuft cells may synthesize and release ACh through different pathways ( Figure 1 ).…”
Section: Acetylcholine Biosynthesis and Release In Tuft Cellsmentioning
confidence: 99%
“…The oscillation of elevated Ca 2+ levels subsequently promotes the release of ACh ( Fu et al, 2018 ). However, bitter and other diverse substances, whether noxious or innocuous, trigger ACh biosynthesis of tuft cells via canonical taste transduction cascade depended on gustducin and TRPM5 ( Saunders et al, 2014 ; Hollenhorst et al, 2020 ). This phenomenon could only be seen in the nasal epithelium.…”
Section: Acetylcholine Biosynthesis and Release In Tuft Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, we found a role for ACh released from non‐neuronal sources as a regulator of airway epithelial ion transport (Hollenhorst, Lips, Weitz, et al, 2012; Hollenhorst, Lips, Wolff, et al, 2012). Since the first studies of the non‐neuronal cholinergic system about 20 years ago (Grando, 1997; Sato et al, 1999; Wessler, Kirkpatrick, & Racké, 1998), it is now well established that ACh plays an important role as autocrine and paracrine signalling molecule in diverse non‐neuronal tissues, including the airway epithelium (Hollenhorst et al, 2020; Perniss, Liu, et al, 2020). ACh transmits its signals via two different classes of receptors: muscarinic (M) receptors and nicotinic receptors (nAChRs) (Lustig, 2006).…”
Section: Introductionmentioning
confidence: 99%